Platelet-Rich Emboli in Cerebral Large Vessel Occlusion Are Associated With a Large Artery Atherosclerosis Source. Issue 7 (July 2019) - Fitzgerald, Seán; Dai, Daying; Wang, Shunli; Douglas, Andrew; Kadirvel, Ramanathan; Layton, Kennith F.; Thacker, Ike C.; Gounis, Matthew J.; Chueh, Ju-Yu; Puri, Ajit S.; Almekhlafi, Mohammed; Demchuk, Andrew M.; et al.
Abstract : Background and Purpose—: Nearly 30% of large vessel occlusion acute ischemic stroke clots are from an unknown source. We assessed histological clot composition in a series of patients with large vessel occlusion and investigated correlations between clot composition and stroke pathogenesis. Methods—: As part of the multi-institutional STRIP registry (Stroke Thromboembolism Registry of Imaging and Pathology), consecutive emboli retrieved during mechanical thrombectomy were stained using Martius Scarlett Blue and analyzed using machine learning software. We assessed proportions of red blood cells, fibrin, platelets, and white blood cells. Correlations between clot components and stroke pathogenesis (large artery atherosclerosis, cardioembolism, and stroke of undetermined pathogenesis) were assessed using SPSS22. Results—: One hundred five patients were included. The proportion of platelet-rich clots (55.0% versus 21.2%; P =0.005) and percentage of platelet content (22.1±4.2% versus 13.9±14.2%; P =0.03) was significantly higher in the large artery atherosclerosis group compared with the cardioembolic group. The proportion of platelet-rich clots (50.0% versus 21.2%; P =0.024) was also significantly higher in the cryptogenic group compared with cardioembolic cases. Large artery atherosclerosis and cryptogenic cases had a similar proportion of platelet-rich clots (55.0% versus 50.0%; P =0.636). There was no significant difference between stroke pathogenesis and the other major clot components. Conclusions—: High platelet content of emboli is associated with a large artery atherosclerosis etiology of large vessel occlusion. Abstract : Supplemental Digital Content is available in the text.